b utobiographical reflections /c - Thinley Norbu (b, 2014)
Personal reminiscences of an esteemed Tibetan Buddhist master, ranging from touching memoir to humorous storytelling, from sharp cultural commentary to deeply felt verse--illustrated with rare photos in full color. Illustrated with color photos published for the first time, this collage of reminiscences affords a rare glimpse into the life of an esteemed Tibetan Buddhist teacher. The author sets a magical mood as he describes his early years in "Snowland" (Tibet) as one of seven children of a renowned Nyingma master. Thinley Norbu Rinpoche's storytelling alternates earthy humor with poetic sensitivity and tender sensuality. Describing his travels in Asia, Europe, and America, he presents thumbnail sketches of people and places, as well as sharp-sighted commentary on Western cultural trends and Dharma students' positive and negative qualities. More than just an autobiography, this written offering is an expression of Rinpoche's wisdom, compassion, and personal realization.
Keywords: Thinley Norbu; Buddhist monks -- Biography; Religion -- Buddhism -- Tibetan